Damage‐Free Charge Transfer Doping of 2D Transition Metal Dichalcogenide Channels by van der Waals Stamping of MoO3 and LiF. Issue 3 (17th January 2022) - Cho, Yongjae; lee, Sol; Cho, Hyunmin; Kang, Donghee; Yi, Yeonjin; Kim, Kwanpyo; Park, Ji Hoon; Im, Seongil
Abstract: To dope 2D semiconductor channels, charge‐transfer doping has generally been done by thermal deposition of inorganic or organic thin‐film layers on top of the 2D channel in bottom‐gate field‐effect transistors (FETs). The doping effects are reproducible in most cases. However, such thermal deposition will damage the surface of 2D channels due to the kinetic energy of depositing atoms, causing hysteresis or certain degradation. Here, a more desirable charge‐transfer doping process is suggested. A damage‐free charge‐transfer doping is conducted for 2D MoTe2 (or MoS2 ) channels using a polydimethylsiloxane stamp. MoO3 or LiF is initially deposited on the stamp as a doping medium. Hysteresis‐minimized transfer characteristics are achieved from stamp‐doped FETs, while other devices with direct thermal deposition‐doped channels show large hysteresis. The stamping method seems to induce a van der Waals‐like damage‐free interface between the channel and doping media. The stamp‐induced doping is also well applied for a MoTe2 ‐based complementary inverter because MoO3 ‐ and LiF‐doping by separate stamps effectively modifies two ambipolar MoTe2 channels to p‐ and n‐type, respectively. Abstract : Damage‐free charge transfer doping methods using MoO3 ‐ and LiF‐deposited polydimethylsiloxane stamp are demonstrated for 2D‐like thin transistor channels. Both p‐MoTe2 and n‐MoS2 channels are successfully doped by such a stamping method, also displaying a hysteresis‐minimized device performance. Because defect‐free doping is hardly achieved by the conventional method using a direct thermal deposition, the stamping method is regarded novel and worthy.